(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Microfinance is a source of financial services for people who are unable to gain access to traditional banking and financial services. Microfinance is based on two ways of being able to deliver financial services to people. Proponents of microfinance believe that this could be the way to help poor people out of poverty. This paper will analyze this relationship and look at the impact of both regulations and supporting institutions on various indicators of MFI performance for a sample of 79 countries. This will be done in order to determine if MFIs in countries with regulations that should be conducive to microcredit, result in a statistically significant increase in cost per borrower. These types of insights are important as the results will highlight a framework of regulation that a country trying to spur economic growth (through microfinance) could implement to create the highest likelihood of success for existing and upstart MFIs. The countries which are sampled are stratified by income, using a classification system created by the World Bank based on gross national income.